2020
DOI: 10.3389/feduc.2020.518209
|View full text |Cite
|
Sign up to set email alerts
|

Music Cognition and Affect in the Design of Technology-Enhanced Music Lessons

Abstract: The present study addresses the lack of an instructional design methodology that guides the integration of technology in music listening and composition activities, and enriches the framework of Technological Pedagogical Content Knowledge (TPCK)an essentially cognitive model-with the affective domain. The authors herein provide many examples that illustrate the music design principles and the expanded Technology Mapping instructional design process that have been proposed in previously published work. The prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 89 publications
(151 reference statements)
0
2
0
2
Order By: Relevance
“…It might be insightful for music educators to consider the underlying issue of boredom, a feature observed in both men (Emo9—Music courses boredom) and women students (Emo10—Music material boredom) when designing and delivering their courses. The introduction of innovative musical technology tools in the classroom has the potential to captivate students' attention and transform music learning into a more engaging process (Macrides & Angeli, 2020). Furthermore, empirical studies have shown that such tools not only enhance the clarity and directness of students' understanding of musical knowledge but also aid in grasping the emotional impacts of music (Macrides & Angeli, 2018a, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be insightful for music educators to consider the underlying issue of boredom, a feature observed in both men (Emo9—Music courses boredom) and women students (Emo10—Music material boredom) when designing and delivering their courses. The introduction of innovative musical technology tools in the classroom has the potential to captivate students' attention and transform music learning into a more engaging process (Macrides & Angeli, 2020). Furthermore, empirical studies have shown that such tools not only enhance the clarity and directness of students' understanding of musical knowledge but also aid in grasping the emotional impacts of music (Macrides & Angeli, 2018a, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…In order to address the challenges of superficial music learning and less‐than‐ideal educational outcomes, often associated with the integration of music technology, it would be beneficial for music educators to consider exploring and thoughtfully implementing promising and engaging music tools. Such exploration and implementation might be most effective when aligned with the Technological Pedagogical Content Knowledge (TPCK) framework and music design guidelines (Macrides & Angeli, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Teniendo en cuenta que es necesaria una gran variedad de recursos y materiales para desarrollar la creatividad (Barrett et al, 2022;Calavia et al, 2021;Davies et al, 2013), el uso de recursos tecnológicos en los proyectos educativos para trabajar la creatividad musical es muy reducido, solo un 2% de las actividades incorporaban recursos digitales. Este dato pone de manifiesto que las editoriales necesitan mayor conocimiento sobre la influencia que tienen las herramientas digitales en el desarrollo de la creatividad musical, tal y como destacan numerosos autores (Addessi, 2020;Cremata & Powell, 2017;Dobson & Littleton, 2016;Macrides & Angeli, 2020;Nikolaidou, 2012;Palazón-Herrera, 2021).…”
Section: Discusión Y Conclusionesunclassified
“…En un estudio realizado por Alonso Vera & Vicente Nicolás (2019), los docentes de música de secundaria opinaban que no utilizar libro de texto permitía una mayor libertad y flexibilidad, la creación de recursos propios y la incorporación de las TIC a la docencia de la música. Diferentes autores afirman que los recursos digitales de música pueden desarrollar la creatividad musical (Addessi, 2020;Cremata & Powell, 2017;Dobson & Littleton, 2016;Macrides & Angeli, 2020;Nikolaidou, 2012;Palazón-Herrera, 2021). Sin embargo, en un estudio realizado por Huovinen & Rautanen (2020) con niños y niñas de 10 a 12 años, compararon los procesos creativos con tablets y con instrumentos, siendo el grupo que utilizó las tablets menos creativo que el que estuvo tocando con instrumentos.…”
Section: Introductionunclassified